1984
DOI: 10.1002/ajh.2830160412
|View full text |Cite
|
Sign up to set email alerts
|

Functional diversity within the suppressor phenotype as defined by monoclonal antibody in T‐cell prolymphocytic leukemia

Abstract: A patient with T-cell prolymphocytic leukemia (T-PLL) is described. The malignant T-cells from the patient were predominantly Leu-2-positive, indicating a suppressor phenotype. The cells were then tested to determine their functional capabilities. The patient's Leu-2-positive cells initially suppressed B-cell proliferation, as predicted by their phenotype but later functioned as T helper cells in the pokeweed mitogen system without a change in phenotype. The cells also responded inadequately to alloantigen and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In the 1980s, several single case reports were described either as T-PLL or as other designations such as T-cell chronic lymphocytic leukemia (T-CLL). [2][3][4][5][6] The morphologic variation and cytogenetic characteristics in a series of patients with T-PLL were also documented, 7,8 and in the early 1990s, the clinical and laboratory features in 78 patients with T-PLL were reported. 9 T-PLL currently is recognized as a distinct T-cell malignancy that is included in the French-American-British (FAB) classification.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1980s, several single case reports were described either as T-PLL or as other designations such as T-cell chronic lymphocytic leukemia (T-CLL). [2][3][4][5][6] The morphologic variation and cytogenetic characteristics in a series of patients with T-PLL were also documented, 7,8 and in the early 1990s, the clinical and laboratory features in 78 patients with T-PLL were reported. 9 T-PLL currently is recognized as a distinct T-cell malignancy that is included in the French-American-British (FAB) classification.…”
Section: Introductionmentioning
confidence: 99%
“…The concurrence of conspicuous red pulp involvement without white pulp infiltration has been described in other T-cell malignancies as well .54 In vitro studies showed that the T-PLL cells of our patient exhibited normal reactivity with PHA and Con-A and duely expressed HLA-DR and IL2 receptor after stimulation. In five of 11 cases tested, the neoplas- 19,22,27,29 cells of our case proliferated after stimulation with candida and tetanus toxoid. We cannot explain this remarkable finding.…”
Section: Discussionmentioning
confidence: 54%